Semilobar Holoprosencephaly with Congenital Oropharyngeal Stenosis in a Term Neonate - Kenji Hishikawa; Hideshi Fujinaga; Chie Nagata; Masataka Higuchi; Yushi Ito (Thieme Medical Publishers, Inc., 2015)
Abstract Background Holoprosencephaly (HPE) is often accompanied by a deficit in midline facial development; however, congenital oropharyngeal stenosis in neonates with HPE has not been reported before. We describe a case of a neonate with prenatally diagnosed semilobar HPE accompanied by congenital oropharyngeal stenosis. Case Report The patient was born at 39 weeks of gestation and developed dyspnea shortly after. Laryngoscopic test revealed oropharyngeal stenosis. Nasal continuous positive airway pressure, high-flow nasal cannula, and nasopharyngeal airway did not resolve her dyspnea; tracheostomy was required. Conclusion Neonates with HPE might be at higher risk of pharyngeal stenosis because of the functional and/or anatomical abnormalities. In the case of dyspnea in neonates with HPE, laryngoscopic evaluation should be considered.